PENGARUH NILAI PELANGGAN DAN KEPERCAYAAN MEREK TERHADAP KEPUTUSAN PEMBELIAN MOBIL ALL NEW HONDA JAZZ DI PEKALONGAN - Khaerudin Khaerudin; Sri Suryoko; Bulan Prabawani (Universitas Diponegoro, 2014)
This research is motivated by the rapid development of automotive industry in Indonesia which makes the level of competition becomes tight. So the car manufacturers continue to make some innovation for their products. This can be seen from the rich variety of brands and types of cars in Indonesia. At present, cars that are in demand is hatchback car segment, because it offers the practicality of moving in the middle of heavy traffic and fuel consumption is quite economical. There are various variants of car hatchback segment in Indonesia. In particular, this study discusses the All-New Honda Jazz hatchback car that become a leader in Indonesia which had sales declined. The purpose of this study was to determine the effect of customer value and brand trust on purchase decisions All New Honda Jazz car in Pekalongan. This type of research is explanatory, with the techniques of data collection through questionnaires. The sampling technique used accidental sampling technique. The sample totaled 84 people who are users of the All New Honda Jazz car in Pekalongan. This research is use quantitative analysis technique (validity test, reliability test, correlation coefficient, simple and multiple regeression analysis, the coefficient of determination, and a significant test (t and F). Then the data is processed by using SPSS (Statistical Package for Social of Science) 16 for Windows. In quantitative analysis resulted in the following regression equation: Y =8,245 + 0,196X1 + 0,280X2. The results of this study are: (1) It is known that the independent variable customer value (X1) has a positive and significant impact on the dependent variable purchase decision (Y). (2) It is known that the independent variables brand trust (X2) has a positive and significant impact on the dependent variable purchase decision. (3) It is known that the independent variable customer value (X1) and brand trust (X2) at the same time (simultaneous) positive and significant impact on purchasing decisions (Y).